Proteína c reativa como guia da duração da terapia antibiótica em pacientes críticos: ensaio clínico randomizado - Isabela Nascimento Borges (2019)
Introduction: The rational use of antibiotics is one of the main strategies to limit the development of bacterial resistance against these drugs. Strategies for controlling and reducing the time of antibiotic therapy have been studied, and the use of biomarkers to guide antimicrobial therapy is a promising approach. Protocols using C-reactive protein (CRP) as a guide were poorly studied in critically ill adult patients, especially when compared to exclusive clinical protocols without the use of biomarkers. In this study, we aimed to compare the effectiveness of antibiotic therapy protocol guided by serum CRP levels versus therapy based on the best practices in antibiotic therapy (Best Practice) in reducing treatment time. Methods: This is a randomized open-label clinical trial conducted in two intensive care units of the Hospital das Clínicas of the Universidade Federal de Minas Gerais. Patients undergoing antibiotic therapy for less than 48 hours were randomly allocated into two groups: i) intervention, whose antibiotic time was guided by CRP levels, and ii) control, whose antibiotic time was defined by best practices in the literature. In the CRP group, antibiotic interruption was recommended after five full days of antibiotic therapy if fell 50% of peak value (if peak 100mg / L) or after three full days of antibiotic therapy if absolute values 35mg / L (if peak <100mg / L). The primary outcomes were duration of antibiotic therapy in the index episode of infection (on days) and antibiotic free days corrected for 1000 days of hospitalization. Analyzes were primarily performed according to intent to treat. Results: One hundred and thirty patients were included: 64 in the CRP group and 66 in the control (Best Practice) group. The mean age was 61 (Q1-Q3, 51-68) years, 52% were male, with SAPS 3 (Simplified Acute Physiology Score 3) of 59 (Q1-Q3, 50-70), and 28-day mortality of 23.1%, with no statistical difference between the groups. The median duration of antibiotic therapy for the first infectious episode was 7.0 (Q1-Q3, 5.0- 8.8) days in the CRP group and 7.0 (7.0-11.3) days in the control group (p = 0.011). In the cumulative suspension curve of antibiotics, a difference in treatment time between groups was identified, with less exposure in the CRP group (p = 0.007). There was 90% adherence to the protocol. In the analysis per protocol, with 59 patients allocated in each group, the median duration of antibiotics was 6.0 (Q1-Q3, 5.0-8.0) days in the PCR group and 7.0 (7.0- 10.0) days in the control group (p = 0.011). Conclusion: Daily levels of CRP allows an apparently safe, costumatized and more restrictive strategy of antibiotic therapy in critically ill infected patients. Further studies are needed to assess its real impact on clinical practice, especially in subgroups of less severe patients.Key words: Sepsis, intensive care unit, anti-bacterial agents, biomarkers, Creactive protein.